Three-component reactions of aromatic amines, 1,3-dicarbonyl compounds, and α-bromoacetaldehyde acetal to access N-(hetero)aryl-4,5-unsubstituted pyrroles - Huang, Wenbo; Wang, Kaimei; Liu, Ping; Li, Minghao; Ke, Shaoyong; Gu, Yanlong (Beilstein Journal of Organic Chemistry, 2020)
N-(Hetero)aryl-4,5-unsubstituted pyrroles were synthesized from (hetero)arylamines, 1,3-dicarbonyl compounds, and α-bromoacetaldehyde acetal by using aluminum(III) chloride as a Lewis acid catalyst through [1 + 2 + 2] annulation. This new versatile methodology provides a wide scope for the synthesis of different functional N-(hetero)aryl-4,5-unsubstituted pyrrole scaffolds, which can be further derived to access multisubstituted pyrrole-3-carboxamides. In the presence of 1.2 equiv of KI, a polysubstituted pyrazolo[3,4-b]pyridine derivative was also successfully synthesized.
Keywords: acid catalyst; [1 + 2 + 2] annulation; KI; pyrazolo[3,4-b]pyridine; pyrroles